How to make grounded the preferred approach to psychological research? A review - ika febrian kristiana; suryanto suryanto; wiwin hendriani (Journal of Educational, Health and Community Psychology, 2019)
Grounded theory has proven to be a very popular methodological choice for researchers in areas such as education, health, and social since 1960. This review aims to identify and describe the use of grounded theory in the field of psychology. The online database was used as a source including psycINFO, ScienceDirect, and Proquest. There are (N = 18) articles resolved through the screening process by setting exclusion or inclusion criteria. The results of the review on the application of grounded theory in psychology research can be grouped in several points including how to write the title of research, research objectives, to step-by-step grounded theory implementation, technically ranging from researcher attitude, role, and treatment to literature, data collection, its findings. Two grounded theory versions are identified (i.e, classic grounded theory and constructivist) and described in detail the technical applications that can be chosen by the researcher by considering the differences (strengths and weaknesses) between the two. Understanding and disciplined and consistent application of grounded theory will help contribute either in the building, developing, or filling the theoretical gaps that exist.Keywords: classic grounded theory, constructivist grounded theory, psychologyÂ